The Fed and the New Economy - Ball, Laurence; Tchaidze, Robert R (American Economic Review, 2002)
This paper seeks to understand the behavior of Greenspan's Federal Reserve in the late 1990s. Some authors suggest that the Fed followed a simple "Taylor rule," while others argue that it deviated from such a rule because it recognized that the "New Economy" permitted an easing of policy. We find that a Taylor rule based on inflation and unemployment does break down in the late 1990s. However, the Fed's behavior appears stable once one accounts for the falling NAIRU of the period. A rule based on inflation and the deviation of unemployment from the NAIRU captures the Fed's behavior through the entire period from 1987 to 2000.